2000
DOI: 10.1128/mcb.20.1.70-80.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Model System for Activation-Induced Alternative Splicing of CD45 Pre-mRNA in T Cells Implicates Protein Kinase C and Ras

Abstract: Multiple isoforms of the protein tyrosine phosphatase CD45 are expressed on the surface of human T cells. Interestingly, the expression of these isoforms has been shown to vary significantly upon T-cell activation. In this report, we describe a novel cell line-based model system in which we can mimic the activation-induced alternative splicing of CD45 observed in primary T cells. Of the many proximal signaling events induced by T-cell stimulation, we show that activation of protein kinase C and activation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 68 publications
(69 reference statements)
7
142
0
3
Order By: Relevance
“…In some cases, it takes several hours for the splice variant mRNA to change significantly, and it has been shown that de novo protein synthesis is required [97,163,164]. Interestingly, the nuclear level of the hnRNP A1 protein is increased in depolarized neurons in regulating the exon 21 (or called C1 cassette exon) of NMDAR1 [72,84].…”
Section: Splicing Factors Regulated By Ca ++ Signalsmentioning
confidence: 99%
“…In some cases, it takes several hours for the splice variant mRNA to change significantly, and it has been shown that de novo protein synthesis is required [97,163,164]. Interestingly, the nuclear level of the hnRNP A1 protein is increased in depolarized neurons in regulating the exon 21 (or called C1 cassette exon) of NMDAR1 [72,84].…”
Section: Splicing Factors Regulated By Ca ++ Signalsmentioning
confidence: 99%
“…Over the past years, the Jurkat-derived Jsl1 T cell line has become a prime model system to investigate activation induced alternative splicing (30,31). A recent RNA-Seq approach in Jsl1 cells suggested an inducible switch in Traf3 isoform expression (3).…”
mentioning
confidence: 99%
“…1B, lanes 2 and 5), however, TPA is known to regulate the splicing of other alternative exons, particularly those of the cell surface molecules CD44 and CD45 [5,6]. We thus tested TPA with more cell lines for Bcl-x splicing changes.…”
Section: Regulation Of Bcl-x Splicing By Il-6 Gm-csf In K562 Cells Amentioning
confidence: 99%
“…Many splice variants have distinct functions and can be regulated by extracellular factors, but the molecular bases of the regulations remain largely unclear [1,4]. In several cases, pre-mRNA elements involved in responses to external factors have been identified [5][6][7][8][9]. In one case, the extracellular signal-regulated kinase (ERK) was found to directly phosphorylate the splicing factor Sam68 in regulating CD44 splicing [10].…”
Section: Introductionmentioning
confidence: 99%